Design of a Novel Dual-Output Multilevel PWM Converter - Aameria K.; Dwivedi D.; Chinmaya K.A. (My University, 2025)
Multilevel converters are substantially replacing the conventional two-level converters due to their ability to meet the higher power demand and improved power quality with lower output THD. They also have nearly sinusoidal output waveforms, lower EMI, higher efficiency, and the requirement of small filters for smoothening the output voltage. However, power electronic converter applications like (EVs and industrial applications) demand compactness and a reduced number of components in the converter, which are generally absent in conventional multi-level converters. If two motor loads or a single six-phase machine needs to be supplied, a conventional multilevel converter uses separate converters connected from the same dc-link voltage. This results in an increased component count and adds to the inverter cost. This leads to the introduction of a Dual-Output multilevel converter. They can supply either two independent three-phase loads or a single six-phase load, making the system more compact, much lighter, and cheaper. This paper introduces a novel dual-output five-level converter topology based on a stacked six-phase five-level converter. The topology significantly reduces the component count. Additionally switching table and capacitor voltage balancing using redundant states of the proposed converter are given. The simulation results are included to verify the validity of the proposed topology. © 2022 IEEE.